Self-reported altruism as predictor for active-empathic listening skills - Marcu, Gabriela Mariana (COUNS-EDU: The International Journal of Counseling and Education, 2020)
While there are many consistent results regarding the altruism – empathy relationship, starting with the empathy-altruism hypothesis (Batson, 2008) and its confirmations or criticism, there is one specific aspect of empathy that has not often been associated with generosity: active listening. Our research hypothesizes that sharing one’s attention in an empathic way (active-empathic listening) might be a skill linked to a person’s generosity. A linear regression established that self-reported altruism (SRA) could statistically significantly predict someone’s active-empathic listening skill (AELS), F(1, 96) = 28,965, p = .0001 and that SRA accounted for 22,4% of the explained variability in AELS. The results confirmed the initial claim and may have an impact in counseling practice, in career decision-making or in other studies on prosocial behavior.